« Professions des parents ? Loisirs ? Projet ? ». Pratiques et regards croisés d’enseignants et d’élèves sur les fiches de renseignements - Audrey Murillo; Julie Blanc; Hélène Veyrac; Philippe Sahuc (Éducation et Socialisation)
The article focuses on the very first lessons of the academic year, in secondary school, when teachers ask students to introduce themselves, either orally or filling fact sheets. Using interactionist and ergonomic approaches, we focus on Teachers’ and Students’ activities, in these moments of self-introducing. We highlight that teachers take information about pupils, information that they use during the school year. In taking this information, teachers try to preserve the face of their students : the information is thus sometimes prevented, disguised, optional, non-normative, or private. However, students are sometimes embarrassed by the questions their teachers ask, and seek to preserve their faces. Finally, we strive for crossing perspectives between Teachers and Students, and show that the foresight of the ones on the others’ activity is limited.